2020
DOI: 10.3122/jabfm.2020.02.190173
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indices for Advance Care Planning in Primary Care: A Scoping Review

Abstract: Background: Patient identification is an important step for advance care planning (ACP) discussions. Objectives: We conducted a scoping review to identify prognostic indices potentially useful for initiating ACP. Methods: We included studies that developed and/or validated a multivariable prognostic index for all-cause mortality between 6 months and 5 years in community-dwelling adults. PubMed was searched in October 2018 for articles meeting our search criteria. If a systematic review was identified from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
6
8
0
Order By: Relevance
“…When they do initiate these conversations, participants described doing so based on their own clinical acumen. Similar experiences have been described in other studies (30,31). Kim et al (2020) showed that the physician's interpretation of a patient prognosis was a key factor in initiating ACP discussions in primary care.…”
Section: Comparison With Existing Literaturesupporting
confidence: 72%
“…When they do initiate these conversations, participants described doing so based on their own clinical acumen. Similar experiences have been described in other studies (30,31). Kim et al (2020) showed that the physician's interpretation of a patient prognosis was a key factor in initiating ACP discussions in primary care.…”
Section: Comparison With Existing Literaturesupporting
confidence: 72%
“…Similar experiences have been described in other studies [36,37]. Kim et al showed that the physician's interpretation of a patient prognosis was a key factor in initiating ACP discussions in primary care [36]. Despite this, a Canadian study of ACP and EOL plans in elderly individuals, who were at a high risk of death in 6 months, described that although > 75% of patients had thought of EOL care, only 47% had completed ACP and less than 30% had discussed their wishes with their family physician.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…When they do initiate these conversations, participants described doing so based on their own clinical acumen. Similar experiences have been described in other studies [36,37]. Kim et al showed that the physician's interpretation of a patient prognosis was a key factor in initiating ACP discussions in primary care [36].…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
“…When they do initiate these conversations, participants described doing so based on their own clinical acumen. Similar experiences have been described in other studies (38,39). Kim et al (2020) showed that the physician's interpretation of a patient prognosis was a key factor in initiating ACP discussions in primary care.…”
Section: Comparison With Existing Literaturesupporting
confidence: 72%
“…Similar experiences have been described in other studies (38,39). Kim et al (2020) showed that the physician's interpretation of a patient prognosis was a key factor in initiating ACP discussions in primary care. Despite this, a Canadian study of ACP and EOL plans in elderly individuals, who were at a high risk of death in 6 months, described that although >75% of patients had thought of EOL care, only 47% had completed ACP and less than 30% had discussed their wishes with their family physician.…”
Section: Comparison With Existing Literaturesupporting
confidence: 72%